Intrauterine calorie restriction affects placental DNA methylation and gene expression - Chen, Pao-Yang (American Physiological Society, 2013)
Maternal nutrient restriction causes the development of adult onset chronic diseases in the intrauterine growth restricted (IUGR) fetus. Investigations in mice have shown that either protein or calorie restriction during pregnancy leads to glucose intolerance, increased fat mass, and hypercholesterolemia in adult male offspring. Some of these phenotypes are shown to persist in successive generations. The molecular mechanisms underlying IUGR remain unclear. The placenta is a critical organ for mediating changes in the environment and the development of embryos. To shed light on molecular mechanisms that might affect placental responses to differing environments we examined placentas from mice that had been exposed to different diets. We measured gene expression and whole genome DNA methylation in both male and female placentas of mice exposed to either caloric restriction or ad libitum diets. We observed several differentially expressed pathways associated with IUGR phenotypes and, most importantly, a significant decrease in the overall methylation between these groups as well as sex-specific effects that are more pronounced in males. In addition, a set of significantly differentially methylated genes that are enriched for known imprinted genes were identified, suggesting that imprinted loci may be particularly susceptible to diet effects. Lastly, we identified several differentially methylated microRNAs that target genes associated with immunological, metabolic, gastrointestinal, cardiovascular, and neurological chronic diseases, as well as genes responsible for transplacental nutrient transfer and fetal development.